RHETORICAL ANALYSIS OF PRESIDENT TRUMP POLITICAL SPEECH IN PALM BEACH, FLORIDA ON JANUARY 3RD, 2020 ON THE KILLING OF QASSEM SOLEIMANI - Reski Amaliah Haming; Jumharia Djamereng; Nuri Emmiyati (Universitas Islam Negeri Sunan Gunung Djati, 2021)
This research analyzes rhetoric which is uttered by President Trump in his political speech in Palm Beach, Florida on January 2020 on the killing of Qassem Soleimani. The analysis involves its context, arguments, and also the effects caused by his speech. The research method used is descriptive qualitative method. The data were taken from the video, the transcript of the speech and the news related to the speech. Martin theory (2014) of rhetorical analysis on political speech and Cicero`s theory in Aristotle (2008) of the classical principle of rhetoric are used to analyze the data. The research results are the rhetorical context of President Trump`s speech is to respond and clarify the killing of Qassem Soleimani; and the accusation of started a war, thus the rhetorical argument shows that the speech used all the classical principle of rhetoric and the rhetorical effect of the speech is escalating the tension in the region. Keywords: Political speech, rhetorical analysis, president Trump, Qassem Soleimani